2010
DOI: 10.1590/s0365-05962010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo quantitativo das células de Langerhans em carcinomas basocelulares com maior e menor potencial de agressividade local

Abstract: BACKGROUNDS -Basal cell carcinoma affects areas of the body that have been exposed to the sun, and this disorder has different clinical and histopathologic presentations. Some of these forms have a higher potential of local aggressiveness, while others have a lower potential. Langerhans cells actively participate in the skin immune system. OBJECTIVES -To quantitatively evaluate the number of Langerhans cells on the epidermis of basal cell carcinoma with lower and higher potential of local aggressiveness and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In the present study, LCs were significantly higher in BCC1 (14±1.92) than BCC2 (4.7±1.23). Similarly, in the study by Santos (2010), the number of LCs was higher in BCC1 (6.70±2.68) than BCC2 (5.05±2.38) (5). Recent studies reported lower numbers of LCs in malignant tumors such as melanoma than normal skin and benign lesions such as actinic keratosis.…”
Section: Discussionmentioning
confidence: 51%
“…In the present study, LCs were significantly higher in BCC1 (14±1.92) than BCC2 (4.7±1.23). Similarly, in the study by Santos (2010), the number of LCs was higher in BCC1 (6.70±2.68) than BCC2 (5.05±2.38) (5). Recent studies reported lower numbers of LCs in malignant tumors such as melanoma than normal skin and benign lesions such as actinic keratosis.…”
Section: Discussionmentioning
confidence: 51%
“…Some studies demonstrated no significant differences in the number of LCs in human BCC skin lesions relative to normal skin; however, an increased number of LCs has been found in the epidermis adjacent to the tumour [29,30]. The higher numbers of adjacent LCs were associated with a lower potential for aggressiveness of the tumour, suggesting that LCs might play a role in limiting tumour growth [31].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, there were fewer CD1a expressing cells in the epidermis adjacent to the tumor versus normal epidermis 87 . Higher levels of Langerhans cells, identified by the S-100 marker, have been associated with less aggressive BCC 119 . Therefore, the presence of mature dendritic cells in the BCC TME may have a protective role.…”
Section: Immune Infiltratementioning
confidence: 99%